Accounting education in Nigerian University: a systematic review of literature on accounting teaching techniques and academic performance / Rahman Yakubu - Yakubu, Rahman (Faculty of Accountancy, 2019)
Accounting profession globally continue to evolve and the need to produce accounting graduate with practical skills call for attention from various stakeholders in educational sectors on the need for higher institutions offering accounting programme to provide curriculum that are practical-oriented and acceptable in business environment. The main objective of this research is to systematically review accounting education viz; accounting teaching techniques and the impact on students’ academic performance. The concern over the quality of academic staff and the knowledge of the subject being taught necessitate the need to strive on how accounting instructors are being prepared to meet the challenges of developing appropriate techniques that will have impact on the students’ academic performance. This review end-up with published articles during the period 1995-2018 and make significant contributions to literature on accounting education as there are little research findings available as to relevant teaching techniques for accounting instructors in Nigerian Universities. From the review, it could be ascertained that educational authority and professional bodies saddled with the responsibility of providing academic blue-print that would place accounting education in Nigeria on limelight by designing a curriculum that are theory and practice-oriented has failed to do the needful rather, it has been more of who dominate the market amongst these bodies. Nevertheless, since accounting programme in Nigerian Universities are for the period of four years; one year could be used for industry training as applicable in other countries and also the need for government to provide adequate funding for research and infrastructural development.